2018
DOI: 10.1186/s40834-018-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant or recently pregnant opioid users: contraception decisions, perceptions and preferences

Abstract: BackgroundMultiple factors are linked to extremely high unintended pregnancy rates among women who use opioids, including various barriers to contraception adherence. These include patient level barriers such as lack of knowledge and education about highly effective contraception, and potential provider barriers. Using a mixed-methods framework to examine the contraception-related perceptions and preferences of opioid using women is a necessary next step to understanding this phenomenon.MethodsA mixed-method s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3,24,25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3,28 Interestingly, we also found that more than half of women with self-reported opioid use in our study chose immediate tier 1 method uptake, of which Data are represented as n (%), unless noted as means in which case it is meanstandard deviation. a Tier 1 contraceptive methods according to the WHO classification 13,14 : female/male sterilization, intrauterine device, and contraceptive implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3,24,25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3,28 Interestingly, we also found that more than half of women with self-reported opioid use in our study chose immediate tier 1 method uptake, of which Data are represented as n (%), unless noted as means in which case it is meanstandard deviation. a Tier 1 contraceptive methods according to the WHO classification 13,14 : female/male sterilization, intrauterine device, and contraceptive implant.…”
Section: Discussionmentioning
confidence: 99%
“…Women who use opioids are at high risk for unintended pregnancy, with rates ranging from 75% to 86%, compared with 51% in the general population. [1][2][3] The Centers for Disease Control and Prevention (CDC) recently reported that the number of American women with opioid use disorder (OUD) admitted to labor and delivery has quadrupled from 1999 to 2014. 4 This increase is reflected in the higher prevalence of neonatal opioid withdrawal syndrome (NOWS) (also referred to as neonatal abstinence syndrome [NAS]) in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other studies demonstrating low use of LARCs among opioid addicted patients from 5-13%. 9,11 Reasons for patient changes in contraceptive methods might include misinformation, mistrust in health care services, lack of appropriate counseling, or cost. Other barriers affect access from a systems level, such as access to BTL or LARC methods.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study revealed that women with OUD generally considered LARCs acceptable, but lifetime use of LARCs ranged from only 5% to 12% due to limited knowledge and access. 14 The exponential rise of opioid use in pregnancy highlights the urgent need to move beyond postpartum family planning to increase contraception access for all reproductive-aged women with OUD. For the vast number not connected to primary care, integrating contraceptive services into alternative points-of-contact represents a promising new harm reduction strategy.…”
Section: Purposementioning
confidence: 99%